Desenvolvimentismo e novo-desenvolvimentismo : raízes teóricas e precisões conceituais - Mollo, Maria de Lourdes Rollemberg (2013)
This paper starts from the conceptualism of New Developmentalism which was proposed by its formulators and their criticism of the "old" developmentalism in order to compare both. It is elaborate in both theoretical and historical levels. In the former, it explores the theoretical streams that contributed to the formulation of economic policies that designated the Latin American developmentalism. In the latter, it focuses on the economic policy of the Brazilian import-substitution industrialization and advocates the impropriety of associating it to the irresponsibility in the management of the foreign exchange, fiscal and monetary policies, as the proposers of New Developmentalism assert. Finally, in a third stage, it resumes the propositions of the New Developmentalism and debates the pertinence of some of its policy propositions based upon theoretical considerations and the Brazilian experience which were mentioned in the previous stages.